CHALLENGES AND IMPACTS: A BIBLIOGRAPHICAL REVIEW ON THE LAG IN LEARNING CAUSED BY THE PANDEMIC - Silva Gusmão, Anderson; Cleyton Felipe Gaudêncio, Anderson; Bonifácio da Silva Júnior, João; Nestor Felipe Gaudêncio, Robson (Revista Gênero e Interdisciplinaridade, 2024)
This work presents a comprehensive literature review focused on the challenges and impacts generated by the pandemic on learning, highlighting the educational gap observed in different contexts. The central objective is to understand the multiple facets of this gap and propose ways to mitigate its effects. The methodology adopted involved the analysis of academic studies, reports from educational organizations and scientific articles published between 2020 and 2023, a period marked by significant interruptions in conventional education due to the restrictions imposed by the pandemic. The theoretical framework is anchored in concepts of pedagogy, educational psychology and sociology of education. The analysis highlights how the pandemic distinctly affected students at different education levels and socioeconomic contexts, highlighting the widening of educational disparities. Furthermore, the work addresses changes in teaching methods, with an emphasis on the abrupt transition to remote teaching and its challenges, such as the lack of adequate infrastructure and the inadequacy of assessment methods. The results show that the learning gap is multifactorial, involving aspects such as a reduction in the quality of teaching, an increase in school dropout rates and the emotional and psychological difficulties faced by students and teachers. The review points to the urgent need for inclusive and adaptive educational policies, which consider both the recovery of lost content and socio-emotional support. Furthermore, it emphasizes the importance of investments in educational technologies and teacher training for more effective hybrid teaching.